The 4-D Model on the Development of English Learning Materials for Islamic Education Learners - Andi Tenrisanna Syam; Dewi Furwana (UIN Sultan Aji Muhammad Idris Samarinda, 2022)
English for Islamic Studies is taught as the general subject in the State Islamic Institute of Palopo. Therefore, the researchers aimed to develop valid English materials for learners of the Islamic education study program. The researchers applied the 4-D model by Thiagarajan et al. It consists of four stages namely, defining, designing, developing and disseminating. There were 68 learners who answered a questionnaire for needing analysis, 23 learners involved in the field try-out, and three lecturers assessed and reviewed the product. Questionnaires and field notes were used as the research instruments. The obtained data were analyzed qualitatively and quantitatively. The researchers created English materials in the form of a textbook in which it consists of ten units. The topics are 5 pillars of Islam, 6 pillars of faith, daily life of a Muslim, Islamic figure, ulul azmi, Amal Ma’ruf Nahi Munkar, halal and haram, Islamic education in Indonesia, Muslim generation, and religious moderation. The data gathered during the trial period revealed that the textbook was suitable to learning process, met the learners’ needs, and it was well-received by the learners. They were engaged, motivated, and excited to complete the activities outlined in the textbook. Therefore, the textbook can be used by lecturers and learners in Indonesia as a learning medium